Comparison of Outcomes of Dexmedetomidine vs Midazolam for Sedation in Mechanically Ventilated Neurosurgical Patients - Sadaf Zehra, Samrah Shafqat, Shahneela Raza, Alina Siddiqui, Sobia Qamer, Shoaib Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the outcomes of dexmedetomidine versus midazolam for sedation in mechanically ventilated neurosurgical patients at Tertiary Care Hospital, Karachi. Study design: Randomized control trial. Place and duration of study: Department of Anesthesia, JPMC, Karachi from 20th November 2020 to 20th May 2021. Methodology: One hundred patients who met the diagnostic criteria were enrolled. Brief history was taken and demographic information was noted. Results: Mean ages and duration of mechanical ventilations in dexmedetomidine group was 49.78±10.54 years and 93.54±10.53 hours while in midazolam group was 50.41±12.39 years and 117.50±15.51 hours. Mean extubation time in the dexmedetomidine and midazolam group was 35.27±0.57 minutes and 48.84±0.53 minutes and statistically the difference was significant (P=0.01). Whereas, mean Ramsay sedation score in the dexmedetomidine and midazolam group was 3.03±0.04 and 3.92±0.06. P-value was 0.01. Conclusion: Dexemedetomidine prove to be drug of good choice for sedation during neurosurgical mechanism as compared to midazolam. It also showed good extubation time and hemodynamic stability. Keywords: Dexmedetomidine, Midazolam, Sedation, Mechanically ventilated, Hemodynamic changes, Neuro-protection